The Suffering Body in Sport : Shifting Thresholds of Pain, Risk and Injury - Young, Kevin, 1959- (Research in the sociology of sport, 2019)
This volume approaches the study of pain, risk and injury in sport from a variety of social scientific perspectives. Contributions focus on the manifestations of pain, risk and injury within sport cultures, and the degree to which the research is rapidly expanding to include new ways of thinking about risky and painful 'suffering' in sport.